Case Report: Reflections on “Tumor Plop” in a febrile hemodialysis patient who had atypical presentation of atrial myxoma as infective endocarditis - Huang, Fangzhong; Huang, Jian; Zhang, Xingzhen; Li, Shuangqing; Zhu, Lingli; Ying, Jun; Zhou, Fang; Zhang, Yingxin; Xu, Xuchun (Frontiers in Cardiovascular Medicine, 2025)
We report a rare case involving a 43-year-old male on long-term hemodialysis who developed infective endocarditis (IE) accompanied by a diastolic “tumor plop” sound and a large atrial mass, a presentation more commonly linked to atrial myxomas. The patient initially experienced an upper respiratory tract infection caused by Type I parainfluenza virus, which progressed to severe pneumonia. During hospitalization, physical examination revealed an atypical diastolic “tumor plop” sound, prompting further evaluation. Echocardiography identified a sizable atrial mass measuring 51 mm × 33 mm × 32 mm, which oscillated between the left atrium and ventricle throughout the cardiac cycle. Blood cultures confirmed a bloodstream infection with Rothia dentocariosa. Concurrently, the patient suffered an embolic stroke, likely due to detachment of the cardiac mass. Clinical findings supported a diagnosis of IE with embolic stroke caused by the atrial mass, rather than an atrial myxoma. The patient underwent surgical removal of the mass along with a full course of antibiotic therapy, which led to a significant improvement in clinical status. This case demonstrates that the clinical features of IE in patients receiving hemodialysis may resemble those of an atrial myxoma, including the unusual “tumor plop” sound. It also illustrates the diagnostic and therapeutic challenges encountered in such cases, where rapid identification and treatment are essential for improving outcomes.